Combination Low-Dose Pilocarpine/Diclofenac Sodium and Pilocarpine Alone for Presbyopia: Results of a Randomized Phase 2b Clinical Trial - Farid M; Rowen SL; Moshirfar M; Cunningham D; Gaddie IB; Smits G; Ignacio T; Gupta PK (Clinical Ophthalmology)
Marjan Farid,1 Sheri L Rowen,2 Majid Moshirfar,3 Derek Cunningham,4 Ian B Gaddie,5 Gerard Smits,6 Teresa Ignacio,6 Preeya K Gupta7 1UCI Health, Irvine, CA, USA; 2NVISION Eye Centers, Newport Beach, CA, USA; 3Hoopes Vision Research Center, Hoopes Vision, Draper, UT, USA; 4Dell Laser Consultants, Austin, TX, USA; 5Gaddie Eye Centers, Louisville, KY, USA; 6Orasis Pharmaceuticals, Ponte Vedra, FL, USA; 7Triangle Eye Consultants, Raleigh, NC, USACorrespondence: Marjan Farid, UCI Health, 850 Health Sciences Road, Irvine, CA, 92617, USA, Tel +1-949-824-2020, Fax +1-855-376-5057, Email mfarid@hs.uci.eduPurpose: To evaluate the efficacy of 0.2% and 0.4% pilocarpine HCl (CSF-1) for the treatment of presbyopia and to determine the contributions of pilocarpine HCl and diclofenac sodium on the efficacy of fixed-dose combination (FDC) formulations.Patients and Methods: This was a Phase 2b, multicenter, randomized, double-masked, parallel-group clinical trial. Adults (45– 64 years) with presbyopia were randomized 1:1:1 to 3 arms (Pilo arm: pilocarpine HCl; Pilo-Diclo FDC arm: pilocarpine HCl with 0.006% diclofenac sodium; Control arm: 0.006% diclofenac sodium). Participants in Pilo and Pilo-Diclo FDC arms received 0.2% pilocarpine HCl (0.2% Pilo or 0.2% Pilo FDC, respectively) from days 1– 8, and 0.4% pilocarpine HCl (CSF-1 or CSF-1-FDC, respectively) from days 8– 15. Primary efficacy endpoint was achievement of ≥ 3-line (15-letter) gain in mesopic, monocular distance-corrected near visual acuity (DCNVA) at 40 cm, 1 hour post-treatment of the study eye on days 8 and 15 in the per protocol (PP) population. Safety endpoints were assessed.Results: One hundred and sixty-six participants were randomized (intent-to-treat, N = 166; PP, n = 160). There were no statistical differences between 0.2% Pilo or 0.2% Pilo FDC versus Control at 1 hour post-treatment on day 8. On day 15, 43.1% and 46.9% of participants receiving CSF-1-FDC (0.4% Pilo FDC) or CSF-1 (0.4% Pilo), respectively, achieved ≥ 3-line gain at 1 hour post-treatment in mesopic DCNVA compared with 16.1% of Control group in the PP population, meeting the primary endpoint (P = 0.0015 and P = 0.0002, respectively). All formulations were well tolerated.Conclusion: CSF-1 demonstrated significant improvements in mesopic DCNVA and favorable safety. Pilocarpine HCl as a single active ingredient, at the concentration of 0.4% (CSF-1), provided a transient, therapeutic effect for presbyopia.Keywords: pilocarpine hydrochloride, presbyopia, minimum effective concentration